Assessing potential impact of avian influenza on poultry in West Africa: a spatial equilibrium model analysis - You, Liangzhi; Diao, Xinshen (International Food Policy Research Institute, 2006)
In this paper, the authors analyze the potential economic impacts of avian influenza (AI) in West Africa, taking Nigeria as an example. They find that, depending on the size of the affected areas, the direct impact of the spread of AI along the two major migratory bird flyways would be the loss of about 4 percent of national chicken production. However, the indirect effect—consumers’ reluctance to consume poultry if AI is detected, causing a decline in chicken prices—is generally larger than the direct effect. The study estimates that Nigerian chicken production would fall by 21 percent and chicken farmers would lose US$250 million of revenue if the worst-case scenario occurred. The negative impact of AI would be unevenly distributed in the country, and some states and districts would be seriously hurt. This study is based on a spatial equilibrium model that makes use of the most recent spatial distribution data sets for poultry and human populations in West Africa. The study shows that, while most of the attention has focused on preventing global influenza pandemic, preventive measures are also needed at the national, subnational, and local levels, because AI could potentially have a huge negative impact on the poultry industry and the livelihood of smallholder farmers in many regions in West Africa.